An innovative method to assess suitability of Nitrate Directive measures for farm management. (March 2018) - Richard, Annabelle; Casagrande, Marion; Jeuffroy, Marie-Hélène; David, Christophe
Graphical abstract: Highlights: A farm-scale method was developed to assess suitability of Nitrate Directive measures for farm management. Nitrate Directive measures are suitable for farm management when they are consistent with both farm structure and strategy. 3 types of farms differ according to the suitability of Nitrate Directive measures for their farm management ranging from cash crop producers with environment preservation strategy to diversified farmers with reducing costs strategy. Measures dealing with fertilization limitation are more suitable for farm management than soil cover and spatio-temporal limitation measures. Farm management should be better considered when designing Water Policy measures to guarantee their impact on water protection. Abstract: Controlling groundwater diffuse pollution induced by agricultural practices remains a significant challenge and has been receiving strong attention in the European Union (EU) for the last 25 years. The EU's Nitrates Directive (91/676EC) and its associated Nitrate Vulnerable Zone (NVZ) legislation were recently revised in France in 2015, requiring farmers to adopt measures and then modify their agricultural practices to protect water resources. Yet these measures are not always implemented in an optimal way, thus limiting improvement of groundwater quality. Based on semi-directive interviews with 14 French farmers, we developed an innovative farm-scale method composed of four steps. First, we described how these farmers implemented Nitrate Directive measures. Second, we evaluated their impact on farm structure and third their consistency with farmer's strategy. Fourth, we assessed their suitability for farm management as an integrative analysis of the previous step. Through this approach, we identified 3 types of farm management. A group of "Beyond Regulation" composed of farmers for whom Nitrate Directive measures are suitable for their farm management. They optimally implement these measures to reduce pressure on groundwater quality. For the second group named "Soft Regulation-constraints", Nitrate Directive measures are less suitable for their farm management because they have another lucrative activity than cash crop production. This group could benefit from a redesign of the measures, changing from means- to result-oriented obligation in order to take into account the local conditions and also their farm management constraints. For the third group, denoted as "Strong Regulation-constraints", ND measures are not suitable for their farm management. The way they implement measures is usually not optimal to reduce pressure on groundwater quality. We suggest that, investing in an "action-learning" program for such farmers could make them understand the usefulness of this regulation and help them to make the measure implementation suitable for their farm management. This farm-scale method could be used further for water management stakeholders to (i) evaluate the suitability of measures from Water Policy for the diversity of farm management or (ii) design suitable measures for the diversity of farm management on a territory subjected to groundwater pollution issue.